ISLAM AND HALAL PRODUCTS: RELIGIOUS COMMODIFICATION AND CONSOLIDATION OF RELIGIOUS IDENTITY AND MUSLIMAH PERCEPTIONS OF HALAL PRODUCT ADVERTISEMENTS IN INDONESIA - Muhammad - Suhadi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
This article discusses Islam and Halal products. Specifically, this article highlights a number of commercial advertisements for halal products that use religious norms as branding in Indonesia. The ad is seen as commodification of religion and consolidation of religious identity, as well as showing the lifestyle of middle-class Muslims. This article also explores the perceptions of young rural Muslim women who are members of the Parit Baru Village Mosque Youth Association regarding Islamic phenomena and halal products. Methodologically, this article is descriptive qualitative research. The data in this study were obtained from the field through direct interviews with a number of Muslim women at the Parit Baru Village Mosque, and also from searching data by collecting various related literature, books, magazines, and data available on the internet, as well as participating in a number of activities in online space such as watching live streaming, online videos and other data related to this research. The results of the study show that Islam is a broad religion, marked by Islamic attention and regulations regarding halal products for consumption by Muslims in their daily lives, which is also an aspect of Islamic teachings. This article also concludes that advertisements for halal products in Indonesia use religious norms as branding to gain profit on the one hand, and indirectly educate middle-class Muslims, especially women, to maintain the use of the hijab as a form of representation of religious identity on the other hand. This can be seen as a form of consolidation of religious identity on the one hand and the commodification of religion on the other.Keywords: Islam, Halal Products, Commodification of Religion, Religious Identity